AN ATTEMPT AT AN ALGEBRAIC THEORY OF CRYSTAL STRUCTURE. PART 4. - Aboav, David A (Image Analysis and Stereology, 2011)
Since, for reasons to be examined in a later instalment of this work, the postulates of Euclid do not seem suited for the purpose, an attempt is made to classify regularities in the observed diffraction of X-rays by matter in the crystalline state on a 'Pythagorean', or purely numerical basis. "I am quite satisfied if we have the machinery for making predictions, even if we are unable to understand it clearly" (Einstein, 1953).